2013
DOI: 10.1038/ejhg.2013.162
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal-dominant nystagmus, foveal hypoplasia and presenile cataract associated with a novel PAX6 mutation

Abstract: Autosomal-dominant idiopathic infantile nystagmus has been linked to 6p12 (OMIM 164100), 7p11.2 (OMIM 608345) and 13q31-q33 (OMIM 193003). PAX6 (11p13, OMIM 607108) mutations can also cause autosomal-dominant nystagmus, typically in association with aniridia or iris hypoplasia. We studied a large multigenerational white British family with autosomal-dominant nystagmus, normal irides and presenile cataracts. An SNP-based genome-wide analysis revealed a linkage to a 13.4-MB region on chromosome 11p13 with a maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 32 publications
2
32
1
Order By: Relevance
“…PAX6 disease may present with complete aniridia or with cataract, ellipsoid iris or other mild iris anomalies (33,34). Waardenburg syndrome patients may also have iris transillumination and may possibly have foveal hypoplasia and nystagmus as well; one patient in our foveal dysplasia category has Waardenburg syndrome with an MITF mutation, and foveal hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…PAX6 disease may present with complete aniridia or with cataract, ellipsoid iris or other mild iris anomalies (33,34). Waardenburg syndrome patients may also have iris transillumination and may possibly have foveal hypoplasia and nystagmus as well; one patient in our foveal dysplasia category has Waardenburg syndrome with an MITF mutation, and foveal hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…15 3.2 Predictive Setting: The tested person is clinically unaffected but carries an increased risk based on family history (To be answered if in 1.9 'B' was marked)…”
Section: Will Disease Management Be Influenced By the Results Of A Genmentioning
confidence: 99%
“…6,7,10,11 Phenotypically subtle PAX6 variants have been documented, [12][13][14] including those that segregate with nystagmus, foveal hypoplasia and autosomal dominant keratitis in the absence of iris abnormalities supporting the concept of gene dosage effects, variable expressivity and gonadal mosaicism. 15 Deep phenotyping studies have revealed smaller corpus callosum area on brain volumetry following magnetic resonance imaging, and subtle hearing difficulties associated with interhemispheric transfer problems. 16 The clinical examination alone in atypical phenotypes would not lead to a PAX6-related molecular diagnosis, highlighting the importance of genetic testing.…”
Section: Clinical Sensitivity (Proportion Of Positive Tests If the DImentioning
confidence: 99%
“…Incidence of nystagmus is as high as 90%, where the majority of these eyes show horizontal pendular nystagmus [1, 63]. Vertical nystagmus as a phenotype variant with foveal hypoplasia, presenile cataract and intact irides has been recently described [68]. …”
Section: Clinical Manifestations and Managementmentioning
confidence: 99%